Dog Hero, tutores e pets: antropomorfismo animal e mobilidades contemporâneas - Barros, Lucas Benegas; Santos, Mateus Augusto dos (Universidade Federal de São Carlos, 2021)
This dissertation summarizes the elements that put on evidence the attenuation of human-animal anthropomorphic relationship due to accentuated mobilities in contemporary society. These phenomenons are discussed in order to analyze and understand how a socio-affective relationship between owners and pets can impact when an individual person wishes to make tourism. In order to achieve this goal, a bibliographic review was made on the subjects of animal anthropomorphism, hospitality, the pet market and mobilities. A case was built, following the content analysis process, in order to understand how the DogHero platform works. It is a startup with an alternative mindset capable of offering a resolution between the fluidity and influidity paradigm of individuals who wants to travel around the world and also be good pet owners. In addiction, a questionnaire was elaborated and disseminated through the google forms platform. The main objective was to understand and correlate the bibliography study and the case with the demand of contemporary dog owners. The conclusion of the study implies the paradox created by anthropomorphism and mobilities impacts directly on how pet owners make tourism and, despite a mindset that approaches the studied elements and prioritizes connection between people to generate trust, the DogHero platform is not recognized by the majority of the owners interviewed on this research. This may put on evidence there are a lot more study subjects to explore about pet market latencies surrounding risk and trust.
Dog Hero, tutors and pets: animal anthropomorphism and contemporary mobilities
Keywords: Mobilidades; Mercado Pet; Antropomorfismo animal; DogHero; Mobilities; Pet market; Pet owners; Tutores; Animal anthropomorphism; CIENCIAS SOCIAIS APLICADAS::TURISMO